2021
DOI: 10.3389/fcvm.2021.697837
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of sST2 in Cardiovascular Diseases: A Systematic Review and Meta-Analysis

Abstract: Biomarkers such as B-type natriuretic peptide (BNP), N-terminal pro-BNP (NT-proBNP), cardiac troponin (cTn), and CK-MB contribute significantly to the diagnosis of cardiovascular disease (CVD). Recent studies have demonstrated that suppression of tumorigenicity 2 (ST2) is associated with CVD, but a meta-analysis of ST2 levels in different CVDs has yet to be conducted. Therefore, the present study aimed to investigate soluble ST2 (sST2) levels in patients with ischemic heart disease (IHD), myocardial infarction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 66 publications
(80 reference statements)
1
37
1
1
Order By: Relevance
“…In a prospective, non-randomized, single-center study, Zagidullin et al demonstrated that, in patients with STEMI, sST2 had a better prognostic value for cardiovascular (CV) mortality at two years in association with NT-proBNP and pentraxin-3 (Ptx-3), rather than alone, or in combination with only one other value [ 172 ]. Additionally, a recently meta-analysis that aimed to evaluate the diagnostic value of sST2 in CV diseases suggested that its prognostic value is often a negative one, and it can predict the LV function after AMI; however, further investigations are required [ 173 ]. A series of studies assessed the cut-off value of sST2 in patients with STEMI undergoing primary PCI for a variety of MACEs at 1 year follow-up (such as impaired myocardial revascularization, HF, all-cause death, non-fatal myocardial infarction and non-fatal stroke), finding mean variation levels greater than 75.8 ng/mL, 58.3 ng/mL or even 2.003 ng/mL (for the revascularization part) [ 173 , 174 , 175 , 176 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a prospective, non-randomized, single-center study, Zagidullin et al demonstrated that, in patients with STEMI, sST2 had a better prognostic value for cardiovascular (CV) mortality at two years in association with NT-proBNP and pentraxin-3 (Ptx-3), rather than alone, or in combination with only one other value [ 172 ]. Additionally, a recently meta-analysis that aimed to evaluate the diagnostic value of sST2 in CV diseases suggested that its prognostic value is often a negative one, and it can predict the LV function after AMI; however, further investigations are required [ 173 ]. A series of studies assessed the cut-off value of sST2 in patients with STEMI undergoing primary PCI for a variety of MACEs at 1 year follow-up (such as impaired myocardial revascularization, HF, all-cause death, non-fatal myocardial infarction and non-fatal stroke), finding mean variation levels greater than 75.8 ng/mL, 58.3 ng/mL or even 2.003 ng/mL (for the revascularization part) [ 173 , 174 , 175 , 176 ].…”
Section: Resultsmentioning
confidence: 99%
“…As early as 2013, sST2 was recommended by the American College of Cardiology and the American Heart Association as a predictor of hospitalization and death in patients with acute and chronic heart failure [21]. Other larger, clinical studies have since been completed, which also demonstrated elevated sST2 levels in patients with congenital [22] and ischemic [23] heart disease as well as with acute coronary syndrome [24,25]. Additionally, in valvular cardiomyopathies, especially in severe AS, sST2 could be positioned as a relevant biomarker for predictions of mortality and as a relevant criterion for adequate risk stratification [26].…”
Section: Discussionmentioning
confidence: 99%
“…ST2 is expressed on cardiomyocytes, and levels of sST2 in serum from animals and humans were elevated after MI (109). Therefore, IL-33 being the only known ligand of ST2 (38), its role in cardiovascular and vascular diseases (34)(35)(36) was investigated. In contrast to the known pro-inflammatory functions of IL-33, IL-33/ST2 signaling protected animals from experimentally induced cardiac failure by antagonizing angiotensin II-induced cardiomyocyte hypertrophy (110).…”
Section: Reparative Roles Of Ilc2s In Cardiac Dysfunctionmentioning
confidence: 99%
“…Although the functions of IL-33 in allergies are well known (29,30), the focus has currently shifted to its role in cancer (31)(32)(33) and cardiovascular diseases (34)(35)(36). IL-33 is one of the most effective cytokines for regulating ILC2s.…”
Section: Introductionmentioning
confidence: 99%